Hedging US stock markets in wake of COVID-19 pandemic - Pösö, Teemu Petteri (My University, 2023)
The purpose of this pro gradu -study is to examine widely regarded hedging assets against S&P 500 stock index during the COVID-19 pandemic. The motivation to study these assets relies on previous literature and unique market conditions of COVID-19 pandemic for markets. Flight-to-quality is often observed during crisis periods when there is turmoil and distress in financial markets. Increased uncertainty drives investors to become more risk-averse and allocate capital in more stable asset classes. Previous literature has indicated that commodities, government bonds and bitcoin could benefit from such phenomenon. Additionally, by pre-emptively alloca-ting portfolio capital to such assets investors could possibly effectively hedge potential losses of one asset with gains on another assets. This study follows methodology introduced by Baur and McDermott (2010) to compare different assets hedging and safe-haven performance during the COVID-19 markets. Such retrospective analysis provides effective tool for this thesis to provide insight to support future investing theses during market uncertainty. The focus is to set on the United States as the largest open markets in the world with data running from 1st of January 2020 till 20th of December 2021. The data is first cleaned to represent same trading days as the New York Stock Exchange trading days, after which daily returns are presented in log-format of which bottom 1%, 5% and 10% quantiles are picked with dummy variables. Identical formulas are used for different assets to determinate the effectiveness to limit the volatility during these trading days in order to find out possible safe haven effectiveness and hedging ability. The obtained results suggest that most of the assets failed to act as safe haven asset during the COVID-19 markets. Only bonds successfully hedged stock market volatility and losses for inves-tors. When compared with previous literature this study does affirm and contradict number of previous studies. These results can be affected by number of factors such as different sample periods and methodological choices. Results do however indicate that U.S. Government bonds with different maturities did act as hedge against S&P 500 stock market index during the sample period. In addition, gold can be regarded as an effective diversifier with S&P 500 stock index.
Keywords: COVID-19; bitcoin; gold; oil; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance; Finance